Long-Term Surgical Outcomes of Glaucoma Drainage Implants in Eyes with Preoperative Intraocular Pressure Less than 19 mmHg - Shahin Hallaj; Jae-Chiang Wong; Lauren E. Hock; Natasha Nayak Kolomeyer; Aakriti G. Shukla; Michael J. Pro; Marlene R. Moster; Jonathan S. Myers; Reza Razeghinejad; Daniel Lee (Journal of Ophthalmology)
Background. This retrospective review reports on patients who underwent glaucoma drainage implant (GDI) surgery and had baseline intraocular pressure (IOP) of ≤18 mmHg with at least one year of follow-up. Methods. Clinical data of 67 eyes of 67 patients were collected from patients’ charts, and the outcomes of GDI were evaluated until 7 years. GDI failure was defined as IOP reduction of less than 20% from the baseline at two consecutive visits three months after surgery, decline to no light perception, or if additional glaucoma surgery was performed. Results. The average age was 65.9 ± 13.2 years. Most cases were male (52.2%), White (53.7%), and had primary open-angle glaucoma (62.7%). Forty-four eyes had prior glaucoma surgery (68.6%) and 46 (68.6%) had severe glaucoma. Though postoperative (postop) IOP changes were insignificant, the average postop number of medications dropped from 2.4 ± 1.4 to 1.9 ± 1.2 medications two years after surgery (p=0.0451). Postop complications (23.9%) included GDI exposure (7.5%), inflammation (4.5%), shallow anterior chamber (4.5%), and strabismus (1.5%). Hypotony was observed in 4 eyes (5.9%), none of which developed hypotony maculopathy. The cumulative one-year failure rate was 56.7%, most of which were due to failure to lower IOP. Conclusion. In patients with baseline IOP ≤18 mmHg who had GDI surgery, though the change in IOP was not statistically significant, the number of medications dropped and visual field progression slowed in a subset of patients with adequate perimetric data. Due to a relatively high rate of complications and limited effectiveness in lowering IOP, GDI should be cautiously used in these eyes.